Third-hand Smoking Beliefs in Patients with Cancer - Remziye Can; Elif Saraç; Esra Yıldız; Şerif Kurtuluş (Thoracic Research and Practice)
OBJECTIVE: Exposure to third-hand smoke (THS) represents an important health concern in many indoor environments. This study was conducted to test the beliefs of cancer patients about THS and to examine associations with effective factors. MATERIAL AND METHODS: This cross-sectional study included 119 patients who were being treated for cancer in the oncology clinic of a University Hospital. The data were collected using a face-to-face questionnaire. This study consisted of the introductory characteristic form and the “Turkish Form of the Beliefs About Third-hand Smoke Scale”. RESULTS: The mean age was 58.52±14.01, with 73% of the participants being female, and 58% reported not smoking. They had a moderate Third-hand Smoke Scale (3.53±0.45). The impact of THS on health was 3.92±0.48 and Persistence in the Environment was 3.21±0.57. Education, smoking, and having cancer relatives were significantly associated with the THS scale scores. CONCLUSION: None of the participants had previously heard of the concept of THS. Beliefs about the harms of THS exposure were moderate. They believed that THS has a more harmful impact on health than its persistence in the environment. Graduate degrees, smoking, and those with cancer relatives believed the harms of third-hand exposure more than the others.